Performance of Single-Hop and Multi-Hop Topologies in IoT-Based Wireless Sensor Networks for Environmental Monitoring - Sulistyawan, Vera Noviana; Muhsin, Muhsin; Hasanah, Uswatun; Suni, Alfa Faridh; Pamungkas, Damar Purba; Santoso, Rizal Budi; Aditama, Kevin Muhammad Tegar; Fauzi, Muhamad Kurniawan (ISB Atma Luhur, 2025)
This study aims to evaluate the performance of an IoT-based Wireless Sensor Network (WSN) system in monitoring temperature and humidity in a modern poultry house. Testing was conducted across two network topologies — single-hop and multi-hop — to analyze data transmission delay and sensor measurement accuracy. The methodology includes measuring the delay from sensor nodes to the sink node and analyzing sensor accuracy by comparing actual temperature and humidity values with sensor readings. The results indicate that the single-hop topology has lower and more stable transmission delays, ranging from 18 ms to 36 ms. In contrast, the multi-hop topology exhibits higher transmission delays, averaging 47.9 ms, due to additional time spent traversing intermediary nodes. In terms of accuracy, the temperature sensor shows minimal deviation from actual values, demonstrating good reliability. However, the humidity sensor exhibits greater variation, necessitating additional calibration or the use of higher-precision sensors. The evaluation using MAPE, RMSE, MSE, and MAE provides further insights into sensor error levels within the system. The uniqueness of this study lies in the comparative analysis of single-hop and multi-hop network performance in a WSN-IoT-based monitoring system. The study's implications emphasize the importance of optimizing network protocols to reduce latency in multi-hop communication and improving sensor accuracy to enhance the reliability of environmental monitoring.